2021
DOI: 10.1161/circulationaha.120.051171
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Tuning of Mitochondrial Respiration Leads to Aortic Aneurysm

Abstract: Background: Marfan syndrome (MFS) is an autosomal dominant disorder of the connective tissue caused by mutations in the FBN1 gene encoding a large glycoprotein in the extracellular matrix called fibrillin-1. The major complication of this connective disorder is the risk to develop thoracic aortic aneurysm (TAA). To date, no effective pharmacological therapies have been identified for the management of thoracic aortic disease and the only options capable of preventing aneurys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 57 publications
(97 reference statements)
2
68
0
Order By: Relevance
“…HAoSMCs transform from a contractile into a synthetic phenotype and induce loose of vascular tone, which is one of the major pathological process in TAA. Thus, the enhancement of HAoSMCs contractility is indicative of the effectiveness of pharmacotherapy for controlling aortic aneurysm ( Oller et al, 2021 ). In this study, we found that NOTCH1 insufficiency in HAoSMCs downregulated the contractile phenotype proteins SM22 and CNN1 under rhythmic strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HAoSMCs transform from a contractile into a synthetic phenotype and induce loose of vascular tone, which is one of the major pathological process in TAA. Thus, the enhancement of HAoSMCs contractility is indicative of the effectiveness of pharmacotherapy for controlling aortic aneurysm ( Oller et al, 2021 ). In this study, we found that NOTCH1 insufficiency in HAoSMCs downregulated the contractile phenotype proteins SM22 and CNN1 under rhythmic strain.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial dysfunction has been closely linked to a variety of cardiovascular disorders, such as heart failure and atherosclerosis. Recent studies found that mitochondrial dysfunction was also related to the development of arterial aneurysm formation ( Cooper et al, 2021 ; van der Pluijm et al, 2018 ; Oller et al, 2021 ). A single-cell transcriptome analysis on aneurysmal human aortic tissue suggested that mitochondrial dysfunction and increased chromatin oxidative phosphorylation (OXPHOS) were found in TAA tissues and insufficient ATP production might not be sufficient for the contractile activities of human aortic smooth muscle cells (HAoSMCs) ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…The pharmacologic potential of NR in TAAs associated with genetic disorders has been investigated [ 221 ]. Using a mouse model with specific deletion of mitochondrial transcription factor A ( Tfam ) in VSMCs, Tfam -deficient VSMCs were observed to acquire a senescent and proinflammatory phenotype together with impairment in their contractile function [ 221 ].…”
Section: In Vivo Cardiovascular Effects Of Nad+-boosting Strategies: Lessons From Animal Modelsmentioning
confidence: 99%
“…The pharmacologic potential of NR in TAAs associated with genetic disorders has been investigated [ 221 ]. Using a mouse model with specific deletion of mitochondrial transcription factor A ( Tfam ) in VSMCs, Tfam -deficient VSMCs were observed to acquire a senescent and proinflammatory phenotype together with impairment in their contractile function [ 221 ]. These mice develop aortic aneurysms, medial degeneration, and lethal dissections, and NR supplementation rapidly raised TFAM levels, improved mitochondrial metabolism, and normalized aortic function and diameter in the Marfan mouse model of TAA.…”
Section: In Vivo Cardiovascular Effects Of Nad+-boosting Strategies: Lessons From Animal Modelsmentioning
confidence: 99%
“…Mitochondrial dysfunction has been closely linked to a variety of cardiovascular disorders, such as heart failure and atherosclerosis. Recent studies found that mitochondrial dysfunction was also related to the development of arterial aneurysm formation ( Cooper et al, 2020; van der Pluijm et al, 2018; Oller et al, 2021 ). A single-cell transcriptome analysis on aneurysmal human aortic tissue suggested that mitochondrial dysfunction and increased chromatin oxidative phosphorylation (OXPHOS) were found in TAA tissues and insufficient ATP production might not be sufficient for the contractile activities of human aortic smooth muscle cells (HAoSMCs) ( Li et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%